Socially Responsible Investment (SRI) initiatives in developing economies: Challenges faced by oil and gas firms in Ghana - Mawuena Akosua Cudjoe; Ahmed Razman Abdul Latiff; Nor Aziah Abu Kasim; Mohammad Noor Hisham Bin Osman (Cogent Business & Management, 2019)
In recent times, firms and countries especially those in the developed economies are moving more into encompassing both voluntary and mandatory initiatives. This new initiative literature argues is relatively superior to the conventional voluntary initiatives prevalent in most developing economies. Although a catch for researchers, evidence from literature suggest that this interest has mainly been directed at finding the factors that encourage firms to engage in socially responsible investment (SRI) initiatives leading to a proliferation of extant literature. This notwithstanding, very little however exists on the Challenges Firms Face When Engaging In These SRI Initiatives Although Literature Gives An Indication Of Its Essence Especially Within Developing Economies. The Purpose Of This Study Is Thus To Explore The Challenges Faced By Oil And Gas Companies Especially In Developing Economies As They Engage In SRI By Delving Into The context-specific challenges they encounter. This is important as these SRI initiatives are seen to augment the efforts of governments within these developing economies. The study uses the interpretive multiple case study approach in achieving the objective of this tudy. The results of the study suggest that not only do the cases face peculiar challenges; undue government interference and financial constraints. But that the government whose effort they augment (with their SRI initiative) is a source of challenge. The findings also give an indication that some internal stakeholders (staff) form powerful stakeholder group that compound the challenges in engaging in SRI.
Keywords: 650; socially responsible investment (SRI); Ghana Stock Exchange (GSE); Ghana; Oil And Gas (O& G) firms; SRI challenges; social and environmental activities